Empirical model for quantification of confidentiality in OO system - Kumar, Rakesh; Hardeep Singh, Dr (International Journal of Engineering and Technology, 2018)
The coupling or aggregation binds together the different entities or components within the system. An external process when takes or try to take the control of the system will be assisted in its action if the underlying system is highly coupled. A highly coupled design degrades the ability of software to defend against exploitation. Thus from a software developerâ€™s point of view, we must provide so much security at design time that no one outside the system should be able to access in unauthorized way. It is to insure that information leakage is minimal (if not zero as is desired theoretically). This research work done quantitatively, describes the ability of object oriented coupling metrics to predict faulty classes. There are two major section of this paper. One section covers the ability of multi layer neuron perceptron model for prediction of faulty classes and in other section we have proposed and validated a statistical model for confidentiality using data set of dif-ferent releases of apache velocity project so as to quantify the effects of coupling on confidentiality of system.Â